Poverty alleviation through agricultural projects: report on a seminar - D'Silva, Emmanuel (World Bank WashingtonUS, 1992)
Looks at strategies, policies and practices that help alleviate rural poverty. Reviews the Asian experience. Examines macro economic policies and poverty; agricultural planning and sector policies; poverty and access to resources; gender and rural poverty; and beneficiary participation; involving the poor in project design and implementation.